Do IMF-Supported Programs Catalyze Donor Assistance to Low-Income Countries? - Bal Gunduz, Yasemin; Crystallin, Masyita (Washington, D.C. : International Monetary Fund, 2014)
This study explores whether IMF-supported programs in low-income countries (LICs) catalyze Official Development Assistance (ODA). Based on a comprehensive set of ODA measures and using Propensity Score Matching approach to address selection bias, we show that programs addressing policy or exogenous shocks have a significant catalytic impact on both the size and the modality of ODA. Moreover, the impact is greatest when LICs are faced with substantial macroeconomic imbalances or large shocks. Nevertheless, when countries attracting similar donor assistance before shocks are matched results for bilateral ODA turn insignificant, suggesting that the catalytic impact is attributed primarily to multilateral ODA.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet